Evaluating IT projects - Shtembari, Eriona, 1981- (Abingdon, Oxon ; New York : Routledge, 2018)
"Project management disciplines have been a part of IT for many years. Why then, are so many challenges still directly associated with how a project is managed? Many projects fail for a myriad of reasons; most, however, stem from poor or inadequate project evaluation and performance appraisal, while, improved project planning and direction is considered to be one of the key factors to IT project success. Eriona Shtembari arranges evaluation methods and techniques into three groups, managerial-financial-and-development. This book explores the process of project evaluation and the purposes of evaluation, given its strong relationship to the success of the project. It examines IT project evaluation; identifies methods and techniques to be used throughout the project life cycle; examines the benefits of project evaluation and proposes a systematic approach/framework of project evaluation to serve as a tool for successful project management. Shtembari analyses the most up-to-date research relating to the process and methods/techniques of project evaluation, throughout the project life cycle. From the systematic literature review, she identifies the most usable methods and techniques in project evaluation and focuses on the adequacy of these methods and techniques in the service sector. The theoretical underpinning of the book, serves as a base to interpret the interviews in the case study and build a theory as to how the project evaluation context relates to the proposed scientific theory. The findings in this book provide solutions for practitioners to help them boost the evaluation framework and consequently improve their IT project management"--
Project evaluation -- Evaluating IT projects -- Methods and techniques of evaluation.
Includes bibliographical references and index.
BBS
Parama
Keywords: Information technology projects -- Evaluation; Project management -- Evaluation; Information technology -- Management; Business & finance